Worse angels - Barron, Laird (Barron, Laird. Isaiah Coleridge, 2020)
"Ex-majordomo and bodyguard to an industrial tycoon-cum-U.S. senator, Badja Adeyemi is in hiding and shortly on his way to either a jail cell or a grave, depending on who finds him first. In his final days as a free man, he hires Isaiah Coleridge to tie up a loose end: the suspicious death of his nephew four years earlier. At the time police declared it an accident, and Adeyemi isn't sure it wasn't, but one final look may bring his sister peace. So it is that Coleridge and his investigative partner, Lionel Robard, find themselves in the upper reaches of New York State, in a tiny town that is home to outsized secrets and an unnerving cabal of locals who are protecting them. At the epicenter of it all is the site of a stalled supercollider project, an immense subterranean construction that may have an even deeper, more insidious purpose. . . "--Provided by publisher.